Tuesday

September 16, 2014

September 16, 2014

Posted by **amy** on Thursday, February 3, 2011 at 4:21pm.

explain answer.

- geometry -
**helper**, Thursday, February 3, 2011 at 5:19pmxz = 72

xy = 5x + 3

yz = 8x - 9

5x + 3 + 8x - 9 = 72

13x - 6 = 72

13x = 78

x = 6

So, for y to be the midpoint of xz,

xy = yz

5x + 3 = 8x - 9

x = 6

5(6) + 3 = 8(6) - 9

30 + 3 = 48 - 9

33 not = 39

y is not the midpoint

**Answer this Question**

**Related Questions**

geometry - write a 2 column proof, Given D is the midpoint of AC, E is the ...

Geometry - Is it possible for AB = 10, BC = 2x + 5 and AC = 5x, given that point...

geometry - B is the midpoint of and D is the midpoint of . Solve for x, given BD...

Geometry; Check answers? - For each graph, find (a)AB to the nearest tenth and (...

geometry - M is the midpoint ofSymbol for segment A B.. Line segment A B, with ...

Math (Geometry) - Square ABCD has M as the midpoint of AB, N as the midpoint of ...

geometry - in triangle GHJ, K(2,3) is the midpoint of GH, L(4,1) is the midpoint...

geometry - Find the other endpoint of a line segment with the given midpoint and...

geometry - In triangle DEF, A(2,3) is the midpoint of DE, B(4,1) is the midpoint...

Geometry - J is the midpoint of Gk, H is the midpoint of GJ and I is the ...